Impact Of Temporal Factors on Food Choices and Purchase Decisions on Online Food Delivery Platforms - Mr. Gaurav Tewari,; Dr. Charu Bisaria,; Dr. Vivek Sharma, (The Bioscan, 2024)
Temporal factors play a significant role in influencing food choices and purchase decisions on online food delivery platforms. This paper explores the impact of time, convenience, price value, safety, psychological and cognitive load, and exposure to TV advertising on calorie consumption behaviour and food choices. The study examines shifts in consumer behaviour between weekdays and weekends, determining significant disparities in the types and frequency of food orders on different days. Online food delivery platforms have transformed how consumers make purchasing decisions and select food. Additionally, it assesses how seasonal changes and special events, such as holidays and special occasions, influence food choices and ordering habits. The research employed a descriptive research design and utilized descriptive statistics to investigate how temporal factors influence consumer buying behaviour. The findings reveal differences in online food preferences over the course of a week, suggesting that online food preferences change gradually towards weekend preferences during the week but abruptly revert to weekday preferences over Sun-Mon. Seasonal changes also affect preferences, with lighter meals in warm months and comfort foods in colder ones. These findings highlight the significance of time in consumer food choices and offer valuable insights for improving marketing, inventory, and menu planning strategies on food delivery platforms. This research enhances understanding of the relationship between time and food consumption in the digital era.